Hubungan Endometriosis dengan Dismenore pada Pasien Poliklinik Obstetri dan Ginekologi di RSUD Dr. Moewardi - Dian Fikri Rachmawan; Tedja Danudjo Oepomo; Nanang Wiyono (Nexus Kedokteran Klinik, 2014)
Background: Generally, reproductive-aged and unpregnant women experience menstruation which is able to be accompanied by dysmenorrhea. Dysmenorrhea prevalence ranged from 1.7% 97% in 106 studies, which is involving 125.249 women. In 20 high-quality studies with representative samples, dysmenorrhea prevalence was reported between 16.8% 81%. Approximately, there were 60% 70% of Indonesian women who experienced dysmenorrhea during menstruation with 15% of them complained that their activities were limited due to dysmenorrhea. One of the significant risk factors that cause dysmenorrhea is endometriosis. Nevertheless, there is no definitive data on dysmenorrhea caused by endometriosis in Indonesia. In fact, endometriosis would greatly impact the quality of life of a woman. The present study aims to determine the association between endometriosis and dysmenorrhea among patients admitted on the Obstetrics Gynecology Clinic of RSUD Dr. Moewardi. Methods: The present study was as an analytical observational study with cross sectional approach. A total of 45 subjects were selected from medical records of RSUD Dr. Moewardi by stratified random sampling technique, which subsequently were divided into 2 groups, namely; 15 patients of endometriosis group and 30 patients of gynecologic malignancies other than endometriosis group. Data was collected by interviewing patients and asking them to fill out the questionnaire. Data was analyzed by using Chi Square test and processed with Statistical Product and Service Solutions (SPSS) 19.00 for Windows. Results: Chi Square test showed OR = 24,182; CI 95% = 2,788 209,764; and p = 0,000. Patients diagnosed by endometriosis are at risk for dysmenorrhea 24,182 times greater than patients with gynecologic malignancies other than endometriosis. Conclusions: There is a significant association between endometriosis and dysmenorrhea among patients admitted on the Obstetrics Gynecology Clinic of RSUD Dr. Moewardi. Keywords: Endometriosis, dysmenorrhea, stratified randim sampling.